Объяснение:
H2SO4 + Na2CO3 = Na2SO4 + CO2↑ + H2O
2H(+) + SO4(2-) + 2Na(+) + CO3(2-) = 2Na(+) + SO4(2-) + CO2↑ + H2O
2H(+) + CO3(2-) = CO2↑ + H2O
H2SO4 + 2KOH = K2SO4 + 2H2O
2H(+) + SO4(2-) + 2K(+) + 2OH(-) = 2K(+) + SO4(2-) + 2H2O
H(+) + OH(-) = H2O
H2SO4 + MgO = MgSO4 + H2O
2H(+) + SO4(2-) + MgO = Mg(2+) + SO4(2-) + H2O
2H(+) + MgO = Mg(2+) + H2O
H2SO4 + Fe = FeSO4 + H2
2H(+) +2e = H2(0) 1 в-ие
ок-ль
Fe(0) -2e = Fe(+2) 1 ок-ие
в-ль
H2SO4 + Zn(OH)2 = ZnSO4 + 2H2O
2H(+) + SO4(2-) + Zn(OH)2 = Zn(2+) + SO4(2-) + 2H2O
2H(+) + Zn(OH)2 = Zn(2+) + 2H2O
Fe2O3 + 6H(+) + 6NO3(-) -> 2Fe(+3) + 6NO3(-) + 3H2O
Fe2O3 + 6H(+) + 2Fe(+3) + 3H2O
FeCl3 + 3KOH -> Fe(OH)3 + 3KCl
Fe(+3) + 3Cl(-) + 3K(+) + 3OH(-) -> Fe(OH)3 + 3K(+) + 3Cl(-)
Fe(+3) + 3OH(-) -> Fe(OH)3
H3PO4 + Fe(OH)3 -> FePO4 + 3H2O
3H(+) + PO4(-3) + Fe(OH)3 -> FePO4 + 3H2O
FeS + 2HCl -> FeCL2 + H2S
FeS + 2H(+) + 2Cl(-) -> Fe(+2) + 2Cl(-)+ H2S
FeS + 2H(+) -> Fe(+2) + H2S
2) 2FeCl3 + 3Ba(OH)2 -> 3BaCl2 + 2Fe(OH)3
2HNO3 + K2CO3 -> 2KNO3 + CO2 + H2O
H2SO4 + Ba(OH)2 -> BaSO4 + 2H2O
LiOH + HBr -> LiBr + H2O